Analisis Faktor-Faktor yang Memengaruhi Nilai Aktiva Bersih Reksadana Syariah (Periode 2016-2019) - Aldiansyah Aldiansyah; Fifi Afiyanti Tripuspitorini; Fatmi Hadiani (Journal of Applied Islamic Economics and Finance, 2021)
This study aims to determine the effect of inflation, Rupiah exchange rate, SBIS yield rate, ISSI on NAV of Islamic mutual funds in Indonesia. The analytical method used is multiple linear regression using secondary data in the form of time series from January 2016 to December 2019. The independent variables analyzed in this study are inflation, rupiah exchange rates, returns on SBIS and ISSI, while the dependent variable is Asset Value. Net Sharia Mutual Funds. The results of this study indicate that inflation has no significant effect on NAV of Sharia Mutual Funds, Exchange Rate, ISSI has a significant effect on NAV of Sharia Mutual Funds, SBIS has a significant effect on NAV of Sharia Mutual Funds in opposite directions